Impact of inventory-based electronic liquidity providers within a high-frequency event- and agent-based modeling framework - Alexandru Mandes (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
This contribution addresses the impact of high-frequency electronic liquidity provision strategies on financial markets' intraday dynamics, by evaluating the interaction between multiple trading strategies within a computer laboratory, i.e. an artificial stock market. Initially, a realistic base-line model is set up around a continuous double auction market, with trading being pursued only by four types of low-frequency market participants. Sequentially, the high-frequency agents are added to the model and the corresponding changes related to various measures of market quality and market systemic risk are analyzed, under both regular and market stress conditions, such as when the order flow balance is suddenly disrupted by a large volume-in-line sell program. A detailed intraday analysis of a flash crash emergence is also conducted. Finally, possible regulatory policies such as minimum holding or quote resting time and financial-transaction taxes are assessed.
Keywords: C63; G17; G28; 330; agent-based modeling; continuous double auction; high-frequency trading; electronic liquidity provision; market quality; systemic risk; flash crash; regulatory policies